The Cultural Values Present in The Oral Literature of Kaili Rai - Mardiah, Mardiah (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2022)
The study "Cultural Values in Kaili Rai Oral Literature in Marana Village, Sindue District" aims to highlight the cultural values contained in Kaili Rai oral literature, which has been largely ignored and is at risk of extinction due to declining numbers of speakers. The research uses qualitative descriptive methods and interviews with local cultural actors to preserve the values and gain a clear understanding of the oral literature. The research findings indicate that some cultural values from the oral literature are still embedded in the everyday lives of community leaders in Marana Village, Sindue District. However, the younger generation has been exposed to outside cultures through electronic media, which has contaminated their understanding of these cultural values. The study's objective is to raise awareness of the importance of preserving regional literature and its cultural values for future generations.